2011
DOI: 10.1007/s10333-011-0276-0
|View full text |Cite|
|
Sign up to set email alerts
|

Fate and transport of bensulfuron-methyl and imazosulfuron in paddy fields: experiments and model simulation

Abstract: Experiments were conducted to determine the fate of bensulfuron-methyl (BSM) and imazosulfuron (IMS) under paddy conditions. Initially, laboratory experiments were conducted and the photolysis half-lives of the two herbicides were found to be much shorter than their hydrolysis half-lives in aqueous solutions. In the aerobic water-soil system, dissipation followed first-order kinetics with water half-lives of 9.1 and 11.0 days and soil halflives of 12.4 and 18.5 days (first phase) and 35.0 and 44.1 days (second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…Since the results of sensitivity analyses depend on the base-case scenarios, 30) four di erent scenarios consisting of the case of four herbicides, mefenacet, 5) pretilachlor, 6) bensulfuron-methyl and imazosulfuron 7) were used in this study. PCPF-1 was previously validated with these four compounds with the actual data sets of water balance and chemical parameters taken from monitoring and experimental studies at the National Institute for Agro-Environmental Sciences (NIAES) in 1998, in Tsukuba, Japan.…”
Section: Pcpf-1 Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the results of sensitivity analyses depend on the base-case scenarios, 30) four di erent scenarios consisting of the case of four herbicides, mefenacet, 5) pretilachlor, 6) bensulfuron-methyl and imazosulfuron 7) were used in this study. PCPF-1 was previously validated with these four compounds with the actual data sets of water balance and chemical parameters taken from monitoring and experimental studies at the National Institute for Agro-Environmental Sciences (NIAES) in 1998, in Tsukuba, Japan.…”
Section: Pcpf-1 Modelmentioning
confidence: 99%
“…e parameter median values of the four pesticides were extracted from previous validation studies using the PCPF-1 model. [5][6][7]43) Normal distributions were attributed to the bulk density 38) as well as the 1st-order dissolution rate and the 1st-order desorption rate constants.…”
Section: Monte Carlo Simulation and Parameter Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports [31][32][33][34] showed that the elimination rate constant of herbicide concentrations in paddy water was assumed to follow biphasic first-order kinetics; an initial rapid-elimination phase followed by a second, slow-elimination phase. In the current study, the turning points between the two phases for herbicides were set to 10 days after application.…”
Section: Herbicide Concentration In the Paddy Watermentioning
confidence: 99%